Synthesis and Characterization of Controlled-Release Urea Fertilizer from Superabsorbent Hydrogels - Salih Muharam; Afria Fitri; Lela Mukmilah Yuningsih; Yulia Mariana Tessa Ayudia Putri; Isnaini Rahmawati (Universitas Gadjah Mada, 2020)
It is very important to develop controlled-release fertilizers to ensure efficiency and environmental protection. This study aims to make a superabsorbent hydrogel-based controlled-release urea fertilizer. Superabsorbent hydrogels were prepared from the cellulose of corn cobs cross-linking with epichlorohydrin, and then an amount of urea as a fertilizer was stored inside the hydrogels (GEL-A). The GEL-A functionalization with carboxy-methyl was also carried out in this study to improve the hydrophilicity of hydrogels (GEL-B). GEL-A and GEL-B were immersed in water at a certain pH and temperature range and the urea concentration released from the hydrogels was monitored by a spectrophotometer. The results showed that the urea released by GEL-A and GEL-B was not much different. Respectively, the urea efficiency of GEL-A and GEL-Bwas around 5.29% and 5.56% for 180 min. The urea released from both hydrogels was not significantly affected by changes in the temperature of the solution. Urea release was influenced by pH, and the rate of urea release of GEL-B was faster than GEL-A, so pH control was needed in the application of this slow-release fertilizer.